MALIGNANCY IN MULTINODULAR GOITER-POST THYROIDECTOMY: A PROSPECTIVE STUDY - Naeem, Fizza; Raza, Sayed Nusrat; Khan, Taimoor Ashraf (Pakistan Armed Forces Medical Journal, 2021)
Objective: To find out the frequency and types of malignancy in patients treated surgically for nontoxic multinodular goiter and its correlation in different age groups and gender. Study Design: Cross-sectional study. Place and Duration of Study: Department of ENT, Combined Military Hospital Rawalpindi, from Dec 2018 to Dec 2019. Methodology: A total of 116 patients operated for nontoxic multinodular goiter were included in the study. Demographic details along with pre-op Ultrasonography findings, Fine Needle Aspiration Cytology, thyroid function test results and post-op histopathological reports of the thyroid specimen were entered on pre-designed proforma. Results were analyzed using the Statistical Package for Social Sciences (SPSS) Version 22. Results: Age ranges from 19 to 70 years (mean 43.51 years). Out of 116 cases operated for multinodular goiter, 37 (31.8%) had malignant thyroid lesions (13 males, 24 females). Papillary carcinoma of the thyroid (45.9%) was the commonest malignancy followed by a follicular variant of papillary carcinoma (24.3%). The most common age group with malignancies was 49-58 years. Conclusion: Malignant Thyroid cancers showed a female preponderance and were most common in age group 49-58 years. Papillary carcinoma of thyroid was the commonest tumor. Radical thyroid surgery is a recommended surgical management option for nontoxic Multinodular goiter.